1980
DOI: 10.1111/j.1651-2227.1980.tb07339.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholic Acid and Chenodeoxycholic Acid Concentrations in Serum During Infancy and Childhood

Abstract: Concentrations of two primary bile acids (cholic and chenodeoxycholic acids) were determined by radioimmunoassay in the serum of infants and children at ages ranging from 1 hour to 15 years. The same bile acids were also measured in umbilical cord serum. Concentrations of the primary bile acids were significantly higher in the serum of 1-hour old infants than those in the umbilical cord serum or the peripheral vein serum of adults. The levels of cholic and chenodeoxycholic acid remained high until the age of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
20
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 17 publications
6
20
0
Order By: Relevance
“…It has also been reported by others that CA and CDCA levels in serum were high in the neonatal period compared to those in other age groups (4,9). Our findings confirm these results, which may be due to prematurity of liver function or to the effect of asphyxia at birth during this period of life (1,4,9,24). The conjugation of bile acids in the liver was presumed to be low in the neonatal period when we started this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It has also been reported by others that CA and CDCA levels in serum were high in the neonatal period compared to those in other age groups (4,9). Our findings confirm these results, which may be due to prematurity of liver function or to the effect of asphyxia at birth during this period of life (1,4,9,24). The conjugation of bile acids in the liver was presumed to be low in the neonatal period when we started this study.…”
Section: Discussionsupporting
confidence: 82%
“…the complex procedure requires a large amount of blood. In recent years, radioimmunoassay has been used for serum bile acids determination (1,4,9) and has provided information on bile acid conjugates. HPLC using a column with immobilized 3a-hydroxysteroid dehydrogenase is suitable for analyzing small amounts of serum for unconjugated and conjugated bile acids separately (20,21) and was, therefore, used to investigate the conjugation pattern of bile acids by age in normal infants and children.…”
mentioning
confidence: 99%
“…From the present study we cannot conclude which of these processes is responsible for the observed correlation between efficacy of fat absorption and intestinal capability to take up LCFA. However, the bile and bile salt compositions have been reported to change during development, both in preterm and term neonates (2,25,27,28), which could be related to the presently obtained results. To elucidate the possible rate-limiting role of biliary LCFA solubilization in a similarly functional study, longitudinal investigations of bile composition in relation to the capability of LCFA uptake would be informative.…”
Section: Discussionsupporting
confidence: 66%
“…In contrast to medium-chain fatty acids, LCFA are almost insoluble in water and heavily depend on solubilization, mainly by bile components, for their efficient transport through the aqueous phase of the small intestine (24). Several studies suggest that neonatal bile formation (in particular, intestinal bile salt concentration) is still insufficient for efficient and complete solubilization of LCFA (2,(25)(26)(27)(28). At present, it is not known whether the translocation of LCFA across the small intestinal membrane or the intestinal capacity to assemble and secrete chylomicrons is rate-limiting in neonatal fat absorption.…”
mentioning
confidence: 99%
“…Hepatic insufficiency with respect to bile acid transport in the fetal state (45) is compcnsated for by the placental transfer of these compounds toward thc mother. The fact that serum bile acid concentrations are markedly increased shortly after birth (37,46,47) supports the idea that the placenta plays a kcy role in the control of fetal cholanemia by compensating the immaturity of biliary function in the fetal liver. The available experimental data are also consistcnt with lcstasis, return to normal in the subsequcnt days or…”
Section: Discussionmentioning
confidence: 64%